Suicidal Ideation Among Adolescents—The Role of Sexual Abuse, Depression, and Impulsive Behavior - Kumar, Pradeep; Srivastava, Shobhit; Mishra, Prem Shankar; Sinha, Debashree (Frontiers in Psychiatry, 2021)
Suicide is the second leading cause of death among adolescents. With every fifth Indian to be an adolescent, the cost of an adolescent dying by suicide is enormous. This necessitates an understanding of the potential risk factors of suicidal ideation among adolescents. Secondary data analysis is performed on cross-sectional survey data obtained from Understanding the Lives of Adolescents and Young Adults. The survey was conducted in two Indian states of Bihar and Uttar Pradesh. Descriptive statistics, bivariate analysis and logistic regression are done to examine the results. Adolescent girls reported more suicidal ideation than boys. The odds of suicidal ideation are significantly higher among adolescents whose mother faced physical abuse and adolescents who themselves experienced sexual abuse. Adolescent boys and girls who have moderate depressive symptoms and impulsive behavior are significantly more likely to report suicidal ideation. The results help in identifying the adolescents who are at a particular risk for suicidal ideation while planning for intervention program for prevention of suicide.